PEDAGOGICAL AND PSYCHOLOGICAL BASIS OF LEARNING A FOREIGN LANGUAGE - Jorayeva Yulduz Roziklovna (Journals Park Publishing, 2024)
This article provides detailed information about methods of learning foreign languages, processes during teaching, and pedagogical and psychological methods.
Keywords: linguodidactics; psychology; pedagogical foundations.